Differences Between Neurotologist and General Radiologist in Reporting High-Resolution Computed Tomography for Otosclerosis - Koycu, Alper; Vural, Omer; Naci Ozluoglu, Levent (ENT Updates, 2023)
Background: To compare the reporting of high-resolution computed tomography of temporal bones for otosclerosis by general radiologists and a neurotologist within a tertiary-care hospital. Methods: A retrospective review of temporal bone high-resolution computed tomography reports of surgically confrmed otosclerosis patients obtained between 2011 and 2020 was performed at a single tertiary-care center. For comparison, the high-resolution computed tomography reports of all patients performed by the general radiologists and the preoperative patient image evaluation notes of the senior neurotologist were reviewed from the medical records. The main outcome measure was the correct identifcation of otosclerosis on HRCT. Results: A total of 42 patients (47 ears) were included in the study. The neurotologist correctly diagnosed otosclerosis in 31 of 47 images (66.0%) and the general radiologists correctly diagnosed otosclerosis in only 3 of 47 images (6.4%). The number of correct diagnoses were signifcantly different when made by the neurotologist and the general radiologist (X² = 25.14, P < .001, McNemar test). Conclusion: The results of this study show that a radiologist without suffcient experience in the feld of neurotology may have a low detection rate of otosclerosis in high-resolution computed tomography of the temporal bone, as is consistent with the literature. In the light of this study, it can be concluded that more experienced eyes (neuroradiologist, neorotologist) are required to diagnose otosclerosis in HRCT than a general radiologist.